The effect of non-verbal music on anxiety in hospitalized children - Ashrafalsadat Hakim; Seyedeh Shima Hosseini Kaldozkhi; Ashraf Tashakori; Saeed Ghanbari (BMC, 2023)
Abstract Background In recent years, the positive effect of non-pharmacological methods such as listening to music in reducing the level of anxiety of hospitalized patients has been reported. This study aimed to determine the effect of non-verbal music on anxiety in hospitalized children. Methods In this study, 52 hospitalized children aged 6 to 12 years were randomly divided into Test and control groups. Research data collection tools included the Spielberger questionnaire to assess the level of anxiety in children. Statistical analysis of data was performed using Chi-square and t-tests by SPSS 23 software. Results Daily listening to non-verbal music for 20 minutes after the second and third days significantly reduced the anxiety score and the number of breaths per minute of hospitalized children (P ≤ 0.01). The trend of changes in anxiety score was measured for three consecutive days and vital signs except body temperature decreased significantly in the test group (P ≤ 0.01). Conclusion According to the results of this study, listening to non-verbal music by hospitalized children can be used as an effective practical method to reduce the level of anxiety and subsequently reduce vital signs.